Five new species of the planthopper genus Atracis Stål (Hemiptera, Fulgoromorpha, Flatidae) from China - Ai, Deqiang; Peng, Lingfei; Zhang, Yalin (European Journal of Taxonomy, 2020)
This paper treats the planthopper genus, Atracis Stål, 1866 (Flatidae: Flatoidinae) in China. Five new species, A. ocularia sp. nov., A. patefacta sp. nov., A. punctulata sp. nov., A. sphaerica sp. nov. and A. ungulata sp. nov., are described and a checklist of all its known species from China is provided.